Nonlinear BAW Filter Effects on the Performance of an LTE Receiver - Silva Cortes, Victor Arturo; Chauhan, Vikrant; Weigel, Robert; Fischer, Georg; Hagelauer, Amelie Marietta (IEEE International Ultrasonics Symposium, 2016)
In this work, the impact of the intrinsic nonlinear effects of BAW filters in the demodulation performance of an LTE receiver is evaluated. The nonlinear effects that shape the generation of higher harmonics in the BAW resonator are covered in a nonlinear model implemented in Keysight ADS and validated through nonlinear measurements done on a BAW resonator for its 2nd harmonic. The nonlinear filter characteristics and its power dependence are captured in a Poly Harmonic Distortion (PHD) model and used for the simulation of the LTE receiver.
elib2cris::1512001600,silva2016a
Keywords: RF frontend; BAW; Nonlinear modeling